2019
DOI: 10.1002/jmri.26854
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant gray matter volumes and functional connectivity in adolescent patients with ADHD

Abstract: Background Altered gray matter (GM) volumes and functional connectivity (FC) happens in attention‐deficit/hyperactivity disorder (ADHD) patients and the intelligence quotient (IQ) of ADHD patients is generally lower than healthy subjects, while few studies have focused on the association among the three. Purpose To investigate the abnormal changes of GM volumes and FC in ADHD patients compared with typically‐developing control (TD‐C), as well as the association between the changes and IQ. Study Type Case contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Brain volumetric analyses show that the GM volume of patients with ADHD was 3% to 5% smaller than that of control subjects (Greven et al, 2015). ADHD has been associated with alterations in both GM volume and WM volume in previous studies (Greven et al, 2015;Zhao et al, 2020). However, Sun et al (2018) reported that no volume difference was found in WM and GM between patients with ADHD and TDCs.…”
Section: The Classification Of Adhd-c Patients and Adhd-i Patientsmentioning
confidence: 85%
See 2 more Smart Citations
“…Brain volumetric analyses show that the GM volume of patients with ADHD was 3% to 5% smaller than that of control subjects (Greven et al, 2015). ADHD has been associated with alterations in both GM volume and WM volume in previous studies (Greven et al, 2015;Zhao et al, 2020). However, Sun et al (2018) reported that no volume difference was found in WM and GM between patients with ADHD and TDCs.…”
Section: The Classification Of Adhd-c Patients and Adhd-i Patientsmentioning
confidence: 85%
“…However, the findings in these studies were inconsistent. Alterations in GM volume, surface area and inward deformation in different regions (such as the left frontal eye field, the left middle cingulum and left cuneus) were reported in patients with ADHD compared with typically developing controls (TDCs) by some groups (Lu et al, 2019; Tang et al, 2019; Zhao et al, 2020), whereas no difference was found in the local distribution of GM by other studies (Ulke et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, there was no effect on the results of the FC analysis. There are also many studies that use datasets with different scan protocols …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that the volume of the precentral gyrus in patients with ADHD is significantly smaller than that of healthy children (Bralten et al, 2016), and the activation of this area is significantly reduced in the process of response inhibition (Lei et al, 2015). Zhao et al (2020) found that patients with ADHD had decreased volume of gray matter in the left superior frontal gyrus, and the functional connectivity between left medial superior frontal gyrus and left superior frontal gyrus was significantly reduced compared to those of HCs. A recent dynamic analysis found that patients with ADHD showed significantly higher temporal variability in the left superior frontal gyrus (medial), left rectus gyrus, left inferior parietal lobule and angular gyrus (Zou & Yang, 2019).…”
Section: Discussionmentioning
confidence: 99%